Overlapping shifts to improve patient safety and patient flow in emergency departments. (November 2022) - Girishan Prabhu, Vishnunarayan; Taaffe, Kevin; Pirrallo, Ronald G; Jackson, William; Ramsay, Michael
Emergency departments (ED) act as primary patient access points for millions of people seeking medical care. However, the sheer volume of patient arrivals and variability among cases makes ED prone to crowding, a well-recognized public health, and patient safety issue. In addition, patient care transitions from one physician to another, known as handoffs, increase with crowding and negatively impact patient safety and satisfaction. This research focused on utilizing a novel hybrid modeling approach to represent the physician and patient activities in the ED to identify physician shift policies that can improve patient safety and patient flow by minimizing handoffs and patient time in the ED. Compared to the current practices that utilize a non-overlapping schedule for staffing the physicians, policies that restrict physicians from taking new patients during the end of their shift can reduce the number of handoffs by as much as 11.2%, with no significant difference in patient time in the ED. Furthermore, comparing current practices to overlapping staffing policies with restrictions, we observed that handoffs and patient time in the ED could be reduced to 41.5% and 14%, with a slight increase in physician full-time equivalents. Finally, we also observed that the ED could immediately accommodate a 10%–15% increase in patient volume with an overlapping staffing policy and still achieve the current performance metrics. However, implementing these policies in a specific ED would call for a risk–cost–benefit analysis considering ED demands, resource availability, and staffing costs.